Two new Platessa (Bacillariophyceae) from Amazonia: Platessa guianensis spec. nov., and P. itoupensis spec. nov. - Tudesque, Loïc; Cohu, René Le; Wetzel, Carlos E. (Phytotaxa, 2016)
Recent investigations in the deep rainforest of Amazonia in French Guiana and in the north of Brazil revealed the presence of two new Platessa species. Detailed light (LM) and scanning electron microscope (SEM) observations were used to describe the morphology and the ultrastructure of these new monoraphid diatoms, Platessa guianensis and P. itoupensis. They display the taxonomic features characteristic of the genus Platessa, namely almost flat valves, straight raphe fissures and uni- to multiseriate striae with specific features such as the ornementation of the striae and the morphology of the groove surrounding the raphe endings. These two Platessa are the first ones described from Amazonia. They are compared with the two types of two similar species described originally from Indonesia (i.e. Platessa brevicostata and Platessa cataractarum) whose original materials are also here re-illustrated in LM and SEM. The taxonomical diagnosis is completed with comments on ecology issues. In addition, we proposed the recombination of three Achnanthes into Platessa based on published literature.